ASPEK HUKUM PENANGANAN KEBAKARAN HUTAN DI INDONESIA - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2007)
Land and forest fires are the phenomenon that are happen every year, both in big and small scale. That fires pounded in almost all of the Indonesia Provinces. The impact of the land and forest fires bring a lot of detriments. such as economy, social, ecology: and educaÂ¬tion as well. This article examines the legal aspect of the land and forest fires handling in IndoneÂ¬sia, which covers administrative, civil, and criminal sanctions. Although the andling of the land and forest fires covers these three sanctions_ in fact its law enforcement is still weak. Kara kunci: penanganan hukum, kehutanan, Baku mutu lingkungan, kebakaran hutan